STATE IN THE HISTORICAL AND INTERNATIONAL LEGAL CONTEXT - V. L. TOLSTYKH (Московский журнал международного права)
The article contains a brief review of the historical genesis of the state and an analysis of its legal characteristics. The author distinguishes four types of state: ancient state, feudal state, modern state and postmodern state. The ideologists of the modern state are J. Bodin, who defined the state through the notion “sovereignty”, and T. Hobbes,who developed the theory of social contract. The Hobbes model was transferred to the international community: the state acting within the international order began to be considered by analogy with the individual acting within internal order - as a subject who had absolute freedom, but voluntarily refused it for the purpose of ensuring safety ant protecting acquired rights. Although international law does not impose strict  requirements on the elements forming the state, it presumes a certain character of the relationship between them. This relationship should be expressed in the sovereign and effective exercise of the government’s power over the population of the state within the territory of the state. A logical defect of the concept of sovereignty is that the absolute nature of state power, on which it insists, contradicts the state’s boundness by international law. In addition, using only one aspect to describe the state (manifestationof the will), it ignores all the others. Indeed the state is not only the government that makes power decisions, but also the product of historical evolution, the cultural space, the national formation, the way to ensure the common good, the scope of the common will, the mechanism of social communication, etc. The author outlines five scenarios for the future. Whichever one is implemented, it is obvious that a society that first formulates a new agenda and implement it will gain the most important geopoliticaladvantages.